2011
DOI: 10.1038/bjc.2011.409
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with metastatic colorectal cancer treated with panitumumab in first- or second-line treatment

Abstract: Background:Panitumumab in combination with chemotherapy was evaluated in two pivotal clinical trials in first- and second-line treatment of metastatic colorectal cancer (mCRC), respectively. This analysis compared the health-related quality of life (HRQoL) of patients with or without panitumumab in the two trials.Methods:Patients with mCRC were randomised to FOLFOX (first-line trial) or FOLFIRI (second-line trial)±panitumumab. The EuroQoL 5-Dimensions Health State Index (EQ-5D HSI) and Visual Analogue Scale (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
4
35
0
1
Order By: Relevance
“…Thus there is no evidence of an association between tumour KRAS/RAS status and toxicity. Furthermore, despite the high incidence of skin toxicity, generic quality of life (QoL) instruments have shown no impact of EGFR inhibitors plus FOLFIRI on overall QoL (Melosky et al , 2009; Bennett et al , 2011; Thaler et al , 2012). Although proactive management of skin toxicity may have reduced the impact for patients, it may also be that the QoL tools used in the study provided too general an assessment to determine the true impact of this AE.…”
Section: Discussionmentioning
confidence: 99%
“…Thus there is no evidence of an association between tumour KRAS/RAS status and toxicity. Furthermore, despite the high incidence of skin toxicity, generic quality of life (QoL) instruments have shown no impact of EGFR inhibitors plus FOLFIRI on overall QoL (Melosky et al , 2009; Bennett et al , 2011; Thaler et al , 2012). Although proactive management of skin toxicity may have reduced the impact for patients, it may also be that the QoL tools used in the study provided too general an assessment to determine the true impact of this AE.…”
Section: Discussionmentioning
confidence: 99%
“…A higher response rate (RR) and longer PFS and OS were seen in patients who developed grade 2–4 skin toxicity versus patients with only grade 0–1 skin toxicity. Despite the large number of grade 3 or higher skin toxicity, panitumumab had no negative effect on overall quality of life (assessed using the EuroQol 5-domain health state index and overall health) [30, 31]. A quality-adjusted time without symptoms of disease or toxicity of treatment (Q-twist) was performed to provide an integrated measure of clinical benefit [32].…”
Section: Efficacymentioning
confidence: 99%
“…No premedication was required and very few infusion reactions (0.7%) and no fatal reactions were observed. Overall health status and health state index were measured using the EQ-5D scales [31]. Health-related quality of life did not differ between the treatment groups.…”
Section: Efficacymentioning
confidence: 99%
“…However, analyses of the HRQoL assessments made during these studies showed no statistically significant or clinically meaningful overall differences in the change in HRQoL in patients treated with panitumumab–chemotherapy compared with those treated with chemotherapy alone [35]. …”
Section: Clinical Evidence Of Pros and Hrqol In Mcrcmentioning
confidence: 99%